History of the Arrival of Islam in the Achipelago: A New Perspective of the Arrival of Islam in the 7th Century - Muhammad Saleh Tajuddin; Andi Tenri Yeyeng; Eliza Farahdiba Saleh (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
This paper discusses the arrival of Islam in the Indonesian archipelago. Four theories regarding the arrival of Islam in the Indonesian archipelago exist: the Arab theory, the Chinese theory, the Indian theory, and the Persian theory. This paper employs qualitative research with a historical and philosophical approach. Data were obtained through a search of books, reputable scientific journals, seminar proceedings, and the internet. The collected data will be analyzed using descriptive analysis techniques. The results of this analysis indicate that of the four theories regarding the arrival of Islam in the Indonesian archipelago, the Arab theory is the strongest, emphasizing that Islam arrived in the Indonesian archipelago in the 7th century AD. This paper is expected to contribute scientifically by providing a new perspective to strengthen the theory that Islam entered the Indonesian archipelago at the beginning of the Hijri century, or the 7th AD.